Malignant Peripheral Nerve Sheath Tumor With Osseous Heterologous Differentiation in Uncommon Locations (Heart and Retropharynx). (August 2016) - Machado, Isidro; Arana, Estanislao; Cruz, Julia; Brotons, Simon; Vendrell, Juan; Escriba, Ismael; Chust, María Luisa; Martínez-Banaclocha, Natividad; Lavernia, Javier; Llombart-Bosch, Antonio
We report two cases of malignant peripheral nerve sheath tumor (MPNST) in an uncommon location (heart and retropharynx) both with divergent osseous heterologous differentiation. We present the pathological and immunohistochemical studies that confirmed the neurogenic origin. The histopathology of the tumor arising in the retropharynx showed a transition from a neurofibroma to MPNST, making this a new report of an MPNST arising from a plexiform neurofibroma without neurofibromatosis. Primary cardiac MPNST with osseous differentiation has never been reported before. In conclusion, the histology of MPNSTs is very heterogeneous, showing no specific diagnostic immunoprofile or genetic alteration. Thus, it is important to rule out other histologically similar tumors, particularly in cases arising in uncommon locations or tumors with divergent heterologous differentiation.